A Comparison Study of Middle Bronze Age II Daggers and Their Rivets as a Tool for a Better Understanding of Their Production. (8th September 2017) - Kan‐Cipor ‐ Meron, T.; Shilstein, S.; Levi, Y.; Shalev, S.
Abstract : The Middle Bronze Age II is a period during which there exists a contemporaneous usage of arsenic copper and tin bronze for metal weaponry production. In order to learn more about the alloys used in this period, the blades and rivets from 65 daggers of two significantly different types, which were discovered at the Rishon LeZion (RL) cemetery, Israel, were tested by the non‐destructive method of X‐ray fluorescence (XRF). The results reveal new knowledge of the alloys selected for dagger and rivet production, both of which represent fine examples of the Middle Bronze Age II Southern Levant in metal industry.